1990
DOI: 10.1182/blood.v76.8.1657.bloodjournal7681657
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of HTLV-I by blood transfusion and its prevention by passive immunization in rabbits

Abstract: To determine the minimum volume of blood required to transmit human T- cell leukemia virus type I (HTLV-I), heparinized blood was collected from a virus-infected female rabbit and aliquots of 10, 5, 1, 0.5, 0.1, and 0.01 mL were transfused into groups of two male rabbits each. All 10 rabbits transfused with 10 to 0.1 mL and 1 of 2 rabbits transfused with 0.01 mL seroconverted for HTLV-I after 2 to 4 weeks. HTLV-I- producing lymphoid cell lines of recipient origin were established from one seroconverted rabbit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…For instance, experiments indicated that passive immunization with an IgG fraction prepared from seropositive asymptomatic carriers prevented HTLV-1 transmission in rabbits. 25 Furthermore, there have been numerous reports of HTLV-1 for ATL development. It has been speculated that not only a high PVL but also male sex is a risk factor for ATL 20 ; however, a contribution of anti-HTLV-1 antibody to ATL development has rarely been described.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, experiments indicated that passive immunization with an IgG fraction prepared from seropositive asymptomatic carriers prevented HTLV-1 transmission in rabbits. 25 Furthermore, there have been numerous reports of HTLV-1 for ATL development. It has been speculated that not only a high PVL but also male sex is a risk factor for ATL 20 ; however, a contribution of anti-HTLV-1 antibody to ATL development has rarely been described.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model, 0.01 mL of blood is sufficient to transmit HTLV-I from rabbit to rabbit. 26 The number of lymphocytes transferred in the experiment was estimated to be 1.7 x lo4. The same group of Japanese investigators has also found that HTLV-I can be transmitted to rabbits by human milk and semen containing an estimated -<6 x lo7 lymphocyte^.^^ HTLV-I transmission to a health care worker via needlestick has been and the large number of HTLV-I-and particularly HTLV-II-infected intravenous drug userszo suggests that the required dose of HTLV-I-and -11-infected lymphocytes for humans may be low.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus likely that neonatal infection with HTLV-I could also be prevented by the maternal antibody. This implication is supported by the evidence that HTLV-I infection of newborn rabbits was prevented by the passive transfer of an immune serum containing anti-HTLV-I IgG antibody (Takehara et al, 1989;Kataoka et aL, 1990).…”
mentioning
confidence: 84%